CAUSES OF REMOVABLE DENTURE BREAKS AND ALLERGIC REACTIONS - Makhmudova Ugiloy Bakhtiyorovna (Journals Park Publishing, 2022)
Patients with partial tooth loss over the age of 50 make up the largest group of persons requiring this type of prosthetic treatment - 40%. At the same time, removable dentures are also used quite frequently in younger patients - 15-20%. This is due to the early loss of some of the front teeth as a result of trauma, decay, or periodontal disease. In order to preserve the healthy teeth, limiting the defect of the tooth row, preference is given to the removable plate denture, which allows to achieve the maximum level of aesthetics. As you know, the main element of the removable denture is the base. The following requirements are imposed on plastics for the bases: to be strong and sufficiently resilient, to retain integrity under the action of alternating loads for a long time, to be easily repaired, not to cause allergic reactions of the oral mucosa. Plastics used in domestic orthopedic dentistry meet most of the requirements. However, there are none that would meet absolutely all requirements. All the basic plastics used in our country belong to the hot-curing materials, i.e. they become hard after the temperature effect.
Keywords: teeth preparation, hyperesthesia, desensitizers, low intensity laser, high intensity laser, adhesive systems, primer, bonding.